Technology readiness level: advancing locally made unmanned vehicles / Azlin Abd Jamil ... [et al.] - Abd Jamil, Azlin; Sarijari, Mohd. Adib; A. Rashid, Rozeha; Pusppanathan, Jaysuman; Ismail, Kamarulafizam; Shamsir, Mohd Shahir (Universiti Teknologi MARA Press (Penerbit UiTM), 2024)
Effective technology commercialization is critical for successful product delivery in the current environment of intense innovation competition. Although market acceptance is a crucial factor in the commercialization process, it is equally imperative to attain the suitable Technology Readiness Level (TRL). Given a lack of research on TRL of locally produced unmanned vehicles, this study aims to address the gap by proposing a comprehensive framework for the TRL of its locally developed products. To construct this framework, the research employed a qualitative approach via two rounds of Semi-Structured Interviews (SSI) and the Delphi Method. The interviews engaged expert inventors in evaluating the extent to which their products meet market needs, reflecting the Expertise Opinion Analysis (EOA). Furthermore, the respondents were involved in accordance with their level of active engagement and successful attainment of ultimate TRL stages in the development of the unmanned vehicles products. The information gathered was analysed with meticulous analysis to create a comprehensive TRL framework specifically designed for unmanned vehicles. The analysis considers variations in TRL and aims to promote the integration of local unmanned vehicles technology into the commercial market, thereby enhancing the effectiveness of technology commercialization in Malaysia, fostering innovation, and driving economic growth in this sector through the proposed framework.